UPSKILL MATH PLUS

Learn Mathematics through our AI based learning portal with the support of our Academic Experts!

Learn more### Theory:

Given two functions \(f(x)\) and \(g(x)\), then the composition \(f \circ g\) is computed as follows:

*Working rule*:

Step 1: Rewrite the given composition as \((f \circ g)(x)\) \(=\) \(f\left(g(x)\right)\).

Step 2: Using the individual functions as a reference, replace the variable \(x\) in the outside function with the inside function.

Step 3: Simplify the obtained function.

Example:

If \(f(x) = x -6\) and \(g(x) = x^2\), then find \(f \circ g\).

**Solution**:

\((f \circ g)(x)\) \(=\) \(f\left(g(x)\right)\)

\(=\) \(f\left(x^2\right)\)

\(=\) \(x^2 -6\)

- A function can also be composed with itself. If \(f\) is a function, then its composition with itself is given by \((f \circ f)(x)\) \(=\) \(f\left(f(x)\right)\).
- The composition of function is not commutative. That is, \(f \circ g\) \(\neq\) \(g \circ f\).

Important!

Example:

If \(f(x) = x - 6\) and \(g(x) = x^2\), then check whether the composition of the two functions are commutative.

**Solution**:

First, let us find \((f \circ g)\).

\((f \circ g)(x)\) \(=\) \(f\left(g(x)\right)\)

\(=\) \(f\left(x^2\right)\)

\(=\) \(x^2 -6\)

Now, let us find \((g \circ f)\).

\((g \circ f)(x)\) \(=\) \(g\left(f(x)\right)\)

\(=\) \(g\left(x - 6\right)\)

\(=\) \(\left(x -6\right)^2\)

\(=\) \(x^2 - 12x + 36\)

It is observed that \(f \circ g\) \(\neq\) \(g \circ f\).

Therefore, the composition of the two functions \(f\) and \(g\) are not commutative.